Combining Behavioral and ERP Methodologies to Investigate the Differences Between McGurk Effects Demonstrated by Cantonese and Mandarin Speakers - Zhang, Juan; Meng, Yaxuan; McBride, Catherine; Fan, Xitao; Yuan, Zhen (Frontiers in Human Neuroscience, 2018)
The present study investigated the impact of Chinese dialects on McGurk effect using behavioral and ERP methodologies. Specifically, intra-language comparison of McGurk effect was conducted between Mandarin and Cantonese speakers. The behavioral results showed that Cantonese speakers exhibited a stronger McGurk effect in audiovisual speech perception compared to Mandarin speakers, although both groups performed equally in the auditory and visual conditions. ERP results revealed that Cantonese speakers were more sensitive to visual cues than Mandarin speakers, though this was not the case for the auditory cues. Taken together, the current findings suggest that the McGurk effect generated by Chinese speakers is mainly influenced by segmental phonology during audiovisual speech integration.